Writing the environment : changing attitudes to the Aotearoa New Zealand Environment : a thesis presented in partial fulfilment of the requirement for the degree of Master of Arts in English at Massey University - Rennie, Jocelyn (Massey University, 2002)
There is a long-standing and irrational opposing discourse between the sciences and humanities as to which is the most relevant discipline for meeting the environmental needs of modern society. In a business, technological and industrially focused growth economy, there seems on the surface little room for writers, poets, historians and philosophers. However, it is in part due to the growth economy, the consumer, capitalist, scientific and industrial society, that our planet is suffering from overpopulation, pollution, and in many cases irreversible environmental degradation. In order for human beings to understand what is happening to the environment and why, and before we can begin to restore the ecological balance, a holistic approach must be fostered between the different disciplines that are involved with environmental issues and in writing the environment. As with the medical profession in an age of specialisation, where the 'bone men' don't talk to the 'muscle men' and the 'muscle men' don't communicate with the psychologists, we are in danger of becoming increasingly fragmented from the planet's ecology of which we are a part and which supports us. Those who write the environment are rediscovering the advantages of an ecological, interdisciplinary discourse.
Keywords: Nature in literature; New Zealand in literature; Environmental protection in literature